Dissipative Landau-Zener tunneling in the crossover regime from weak to strong environment coupling - X. Dai; R. Trappen; H. Chen; D. Melanson; M. A. Yurtalan; D. M. Tennant; A. J. Martinez; Y. Tang; E. Mozgunov; J. Gibson; J. A. Grover; S. M. Disseler; et al. (Nature Communications, 2025)
Abstract Landau-Zener tunneling, which describes the transition in a two-level system during a sweep through an anti-crossing, is a model applicable to a wide range of physical phenomena. Realistic quantum systems are affected by dissipation due to coupling to their environments. An important aspect of understanding such open quantum systems is the relative energy scales of the system itself and the system-environment coupling, which distinguishes the weak- and strong-coupling regimes. Using a tunable superconducting flux qubit, we observe the crossover from weak to strong coupling to the environment in Landau-Zener tunneling. Our results confirm previous theoretical studies of dissipative Landau-Zener tunneling in the weak and strong coupling limits. We devise a spin bath model that effectively captures the crossover regime. This work is relevant for understanding the role of dissipation in quantum annealing, where the system is expected to go through a cascade of Landau-Zener transitions before reaching the target state.